Assessing organ-level immunoreactivity in a rat model of sepsis using TSPO PET imaging - Martinez-Orengo, Neysha; Tahmazian, Sarine; Lai, Jianhao; Wang, Zeping; Sinharay, Sanhita; Schreiber-Stainthorp, William; Basuli, Falguni; Maric, Dragan; Reid, William; Shah, Swati; Hammoud, Dima A. (Frontiers in Immunology, 2022)
There is current need for new approaches to assess/measure organ-level immunoreactivity and ensuing dysfunction in systemic inflammatory response syndrome (SIRS) and sepsis, in order to protect or recover organ function. Using a rat model of systemic sterile inflammatory shock (intravenous LPS administration), we performed PET imaging with a translocator protein (TSPO) tracer, [18F]DPA-714, as a biomarker for reactive immunoreactive changes in the brain and peripheral organs. In vivo dynamic PET/CT scans showed increased [18F]DPA-714 binding in the brain, lungs, liver and bone marrow, 4 hours after LPS injection. Post-LPS mean standard uptake values (SUVmean) at equilibrium were significantly higher in those organs compared to baseline. Changes in spleen [18F]DPA-714 binding were variable but generally decreased after LPS. SUVmean values in all organs, except the spleen, positively correlated with several serum cytokines/chemokines. In vitro measures of TSPO expression¬ and immunofluorescent staining validated the imaging results. Noninvasive molecular imaging with [18F]DPA-714 PET in a rat model of systemic sterile inflammatory shock, along with in vitro measures of TSPO expression, showed brain, liver and lung inflammation, spleen monocytic efflux/lymphocytic activation and suggested increased bone marrow hematopoiesis. TSPO PET imaging can potentially be used to quantify SIRS and sepsis-associated organ-level immunoreactivity and assess the effectiveness of therapeutic and preventative approaches for associated organ failures, in vivo.